The Islamic world and the West : an introduction to political cultures and international relations - Hafez, Kai, 1964-; Kenny, Mary Ann (Social, economic, and political studies of the Middle East and Asia ;, 2000)
This anthology is an introduction to political cultures in the Islamic world and into relations between the West and Islam. It outlines similarities and differences in the understanding, perception and communication of politico-ideological issues like modernity democracy and human rights.